Orexin-A differentially modulates inhibitory and excitatory synaptic transmission in rat inner retina. (1st April 2021) - Ruan, Hang-ze; Wang, Li-Qing; Yuan, Fei; Weng, Shi-Jun; Zhong, Yong-Mei
Abstract: In this work, modulation by orexin-A of the release of glutamate and GABA from bipolar and amacrine cells respectively was studied by examining the effects of the neuropeptide on miniature excitatory postsynaptic currents (mEPSCs) and miniature inhibitory postsynaptic currents (mIPSCs) of rat retinal ganglion cells (GCs). Using RNAscope in situ hybridization in combination with immunohistochemistry, we showed positive signals for orexin receptor-1 (OX1 R) mRNA in the bipolar cell terminals and those for orexin receptor-2 (OX2 R) mRNA in the amacrine cell terminals. With whole-cell patch-clamp recordings in rat retinal slices, we demonstrated that application of orexin-A reduced the interevent interval of mEPSCs of GCs through OX1 R. However, it increased the interevent interval of mIPSCs, mediated by GABAA receptors, through OX2 R. Furthermore, orexin-A-induced reduction of mEPSC interevent interval was abolished by the application of PI-PLC inhibitors or PKC inhibitors. In contrast, orexin-A-induced increase of GABAergic mIPSC interevent interval was mimicked by 8-Br-cAMP or an adenylyl cyclase activator, but was eliminated by PKA antagonists. Finally, application of nimodipine, an L-type Ca 2+ channel blocker, increased both mEPSC and mIPSC interevent interval, and co-application of orexin-A no longer changed the mEPSCs and mIPSCs. We conclude that orexin-A increases presynaptic glutamate release onto GCs by activating L-type Ca 2+ channels in bipolar cells, a process that is mediated by an OX1 R/PI-PLC/PKC signaling pathway. However, orexin-A decreases presynaptic GABA release onto GCs by inhibiting L-type Ca 2+ channels in amacrine cells, a process that is mediated by an OX2 R/cAMP-PKA signaling pathway. Highlights: Orexin-A increases glutamate release onto GCs from BCs, acting via presynaptic OX1 R. This modulation is mediated by activation of PI-PLC/PKC signaling pathway in BCs. Orexin-A suppresses GABA release onto GCs from amacrine cells via presynaptic OX2 R. Activation of cAMP-PKA signaling pathway mediates this type of modulation. L-type Ca 2+ channels are involved in the orexin effects on synaptic transmission to GCs.